Progress of Electrochemical Hydrogen Peroxide Synthesis over Single Atom Catalysts - Gao, Jiajian; Liu, Bin (ACS materials letters, 2020)
The electrochemical oxygen reduction reaction (ORR) via the two-electron pathway provides a promising approach for the direct synthesis of hydrogen peroxide (H2O2) and its on-site utilizations. The effective electrocatalyst is one of the key factors determining the future applications of this technology. In recent years, various catalysts, such as pristine carbon materials, modified carbon materials (oxidized or heteroatom doped such as nitrogen, fluorine, or sulfur doped), gold, or mercury alloyed palladium or platinum nanoparticles, as well as transition metal single atom catalysts (SACs) have been reported to effectively catalyze the H2O2 production via the two-electron ORR process. Among these candidates, SACs with 100% atom utilization and well-defined active centers attracted extra attention due to their high catalytic performance for H2O2 synthesis. In this review, the thermodynamics, oxygen molecular activation, and theoretical screening and prediction of SACs for electrochemical H2O2 synthesis are discussed. The catalytic performance, reaction kinetics and mechanism of SACs together with electrochemical devices for H2O2 synthesis via the two-electron ORR are summarized. It is hoped that this contribution can offer a comprehensive reference for the progress of SACs in H2O2 electrochemical production process.